+0  
 
0
42
1
avatar+83 

Use the Remainder Theorem to find the remainder when P(x) = x4 − 9x3 − 5x2 − 3x + 4P(x) = x4 - 9x3 - 5x2 - 3x + 4  is divided by x+3

 Feb 1, 2019
 #1
avatar+96080 
+1

 

 

Put   x = -3  into the function and we have that

 

(-3)^4 - 9(-3)^3 - 5(-3)^2  - 3(-3) + 4 =

 

81 + 243 - 45 + 9 + 4 =

 

292  = the remainder

 

cool cool cool

 Feb 1, 2019

31 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.